Feminisme Neoliberal dan Pseudo-Empowerment dalam Kampanye Kecap ABC “Suami Sejati Mau Masak” - Danadharta, Irmasanthi (representamen, 2021)
This paper tried to give an in-depth critical view on the Kecap ABC Real Husband Cooks Campaign. The campaign tried to tackle the issues within Hill Asean Reports on Gender Inequality in the Domestic Sphere by encouraging men’s participation in the kitchen. The campaign, though were highly praised to be considered as progressive and pro-equality, also send message of pseudo-empowerment within their Neoliberal Feminist message regarding women’s position in the domestic sphere. This paper founds three issues in related to the topic: first is how this campaign fails to eliminate the stereotype of women as weak and dependent towards men although they tried to present women and men as independent. Second, the campaign over simplify gender inequality and went with the neoliberal feminist understanding on individualization of understanding and defining an issue. Last, by putting men in the kitchen will give a message that men are willing and committed to participate in a pro-equality movement but in reality, it is not more than just a pseudo-empowerment created from adding domestic work as a skill. This paper will use Sara Mills’ Critical Discourse Analysis to describe the message stated before within the campaign.   Keywords: Neoliberal Feminism, Discourse Analysis, Sara Mills, Kecap ABC Commercials